Chemical constituents and antioxidant activity of Britton's wild petunia (Ruellia brittoniana) flower - GRACIA LASMA ROHANA SIANTURI; ELYNA WAHYU TRISNAWATI; MAMORU KOKETSU; VENTY SURYANTI (Society for Indonesian Biodiversity, 2023)
Abstract. Sianturi GLR, Trisnawati EW, Koketsu M, Suryanti V. 2023. Chemical constituents and antioxidant activity of Britton's wild petunia (Ruellia brittoniana) flower. Biodiversitas 24: 3665-3672. Britton's wild petunia orkencana ungu (Ruellia brittoniana), which has purple flowers, is widely used as a decorative plant. Isolation and structure determination of the antioxidant compound of R. brittoniana flower were carried out. Extraction was carried out by maceration, and compound isolation was conducted by column chromatography. Structure elucidation was accomplished by FTIR, NMR, and MS Spectrometry. Apigenin (4',5,7-trihydroxyflavone) was isolated from the B1 fraction using chloroform: methanol (10: 1) eluent. Fraction A1, obtained from elution by chloroform: methanol (10: 0), consisted of 24 compounds. Two compounds were identified as 1-hexadecanol and 1-phenyl ethanone, which have antioxidant properties of fraction A1. Fraction B2 was eluted by chloroform: methanol (10:1), consisting of 20 compounds. A compound was identified as 2-methoxy phenol, contributingto the antioxidant properties of fraction B2. The total phenolic content of R. brittoniana flower extract was 1.033 mg GAE/g, and its total anthocyanin content was 16.97%. Fractions A1 and B2 possessed strong antioxidant activities due to their phenolic compounds. Apigenin has three -OH groups in the 4’, 5, and 7 positions; only the -OH group at the 4’ position contributes to its antioxidant activity. Therefore, apigenin has moderate antioxidant activity by DPPH assay. The modification structure of apigenin needs further study to enhance its antioxidant activity. This research shows that R. brittoniana flower can be a source of apigenin, also known to have anticancer properties.